Type 2 diabetes mellitus: a risk indicator for colorectal cancer - Ahmed, Sabrina; Khandker, Salamat; Chowdhury, A. B. M. Alauddin; Roby, Naym Uddin; Miura, Katsuyuki; Ahmed, M. S. A. Mansur (International Journal Of Community Medicine And Public Health, 2020)
Background: Worldwide, colorectal cancer is the fourth most common cancer and affects both men and women equally. Increasing evidence suggests that abnormal glucose metabolism may be associated with increased risk of colorectal cancer. The aim of this case control study was to determine the association of colorectal cancer with type 2 diabetes mellitus (T2 DM) and other risk factors of colorectal cancer among adult Bangladeshi population. Methods: We included patients of colorectal cancer as cases and the controls were mostly cancer patients other than colorectal cancer and relatives of the patients attending in National Institute of Cancer Research Hospital (NICRH) in Dhaka. Three hundred samples (100 cases and 200 controls) were selected purposively. Results: It was found that in cases 19% participants had T2 DM before colorectal cancer whereas 10.5% participants in controls had similar history. Appropriate statistical analysis reported that cases having T2 DM has 2.86 times higher chance to develop colorectal cancer (OR 2.68, 95% CI: 1.21-5.96) compared to controls. We also got significant inverse association with colorectal cancer with obesity (OR 0.43, 95% CI: 0.19-0.97), positive smoking history (OR 0.32, 95% CI: 0.19-0.60) and low fruits and vegetable intake (OR 0.33, 95% CI: 0.19-0.60). Conclusions: This was a unique study for Bangladesh which showed results consistent with the finding of studies done globally. Therefore, we accept our research hypothesis as T2 DM is a risk indicator for colorectal cancer, however obesity, smoking and less fruits and vegetable intake are also risk factors for colorectal cancer among Bangladeshi population.